2021
DOI: 10.3390/ijerph181910470
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Burnout Syndrome and Resilience in Nurses throughout the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Background: The COVID-19 pandemic has contributed to the occurrence of work-related stress on nursing staff. Being resilience an essential element to countering adversity. The aim of the study was to assess burnout syndrome as well as resilience in hospital-care nurses during the first outbreak of the COVID-19 pandemic. Methods: A cross-sectional descriptive study of burnout syndrome and resilience of 101 nurses during the first COVID-19 outbreak. The Maslach Burnout Inventory and the Scale of Resilience of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 29 publications
2
33
0
9
Order By: Relevance
“…Burnout varies depending on context. During the COVID-19 pandemic, for instance, burnout components in health workers have been predicted by a wide variety of factors, such as: emotional exhaustion , by anxiety, the burden of treating suspected COVID-19 patients, depression, fear of infection, marital status, sex; depersonalization , by anxiety, endless months of work in the current department, depression, job category, dissatisfaction with work environment; and personal accomplishment , by job stress, socioeconomic status, workload of directly interacting with patients [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout varies depending on context. During the COVID-19 pandemic, for instance, burnout components in health workers have been predicted by a wide variety of factors, such as: emotional exhaustion , by anxiety, the burden of treating suspected COVID-19 patients, depression, fear of infection, marital status, sex; depersonalization , by anxiety, endless months of work in the current department, depression, job category, dissatisfaction with work environment; and personal accomplishment , by job stress, socioeconomic status, workload of directly interacting with patients [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies compared the frequency of BS between physicians and nurses [62][63][64]. Other studies indicated the prevalence of BS among nurses [20,[65][66][67][68][69]. Aspects such as resilience [70], depression [71], trauma [72], and the role of leadership [73] were also observed in the articles.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies associate BS with the intention to leave and the increased turnover [ 15 , 16 , 17 , 18 , 19 ]. However, the COVID-19 pandemic considerably raised the demand for nurses to perform their activities with quality [ 20 ]. Frontline professionals involved in treating patients with COVID-19 reported increased insomnia and poorer health [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gauti rezultatai parodė, kad slaugytojai, slaugantys COVID-19 sergančius pacientus, pasižymėjo didesniu perdegimo lygiu nei slaugytojai, kurie neslaugė COVID-19 sergančių pacientų. Pastebėta, kad slaugytojai, dirbę su COVID-19 liga sergančiais pacientais, pasižymėjo mažesne saviverte, lyginant su to nedariusiais slaugytojais [14].…”
Section: Covid-19 Pandemijos įTaka Slaugytojų Perdegimo Sindromuiunclassified